Uma contribuição ao estudo do ensino de educação física à distância - Aranha, Amaury José Alves [UNESP] (2014)
The more general aim of this thesis was organizing in countering important economic issues on private HEIs, including sustainability issues, when projected revenue and profits for various scales of enrollments, with valuation issues and quality of courses. So pursuing the hypothesis that undergraduate courses in Physical Education from a distance, could not get good levels of quality, if the pole-face meetings were not well equipped to practical classes. Thousands of people today are already using internet as a means for acquiring knowledge. Distance learning is very recent and its scope cannot be well established. The evolution of this type of education was only possible due to the advancement of technologies related to internet. This type of education has proven to be very attractive for institutions and people. The perceived expansion of distance graduations is already impacting institutions of higher education but since this is a recent expansion, there needs to be a more complex study and research in all fields related to distance learning. This thesis aimed at researching infrastructure and pedagogical aspects in the distance learning area, and understanding the impact of economical results in higher education institutions that offer undergrad distance learning courses in Physical Education